Exploring the Impact of Information and Communication Technology in Regions of Kazakhstan - Kireyeva, Anel A.; Nurbatsin, Akan S.; Mussabalina, Dinara S. (Economy of Regions, 2021)
The research aims to assess the impact of information and communication technology (ICT) on economic growth in different regions of Kazakhstan. A few basic complex methods, such as systematisation of statistical data and regression analysis, conducted using the STATA software package, were used to analyse the relationship of indicators in different periods. Based on data for the period 2007-2018 obtained from the World Bank, the International Telecommunication Union and statistical yearbook of Kazakhstan, we assess how ICT, expressed by such indicators as Internet access in organisations, the number of computers and fixed telephones, influences economic growth. Our analysis revealed differences in the speed of implementation and development of ICT depending on the region, meaning that the least developed territories still lag in the number of Internet users. We have concluded that since 2014, the country’s currency has weakened due to the decrease in the cost of oil and consequent economic decline; mobile devices are increasingly used, reducing the demand for fixed telephones; computers in organisations are affecting economic growth in more developed regions since 2014, although the negative effect of Internet access is growing, as the model shows. The obtained results can used for strategy development to compare economic growth in regions with low, medium, and high development rates.